The Happy Spiritual Intervention for Overcoming Intolerance of Uncertainty among Families of Patients with Mental Disorders - Dwidiyanti, Meidiana; Sawitri, Dian Ratna; Munif, Badrul; Fitri, Anindiyani; Wijayanti, Diyan Yuli (Fakultas Ilmu-ilmu Kesehatan, 2024)
Families of patients with mental disorders frequently experience intolerance of uncertainty due to prolonged treatment, high caregiving burdens, and unpredictable patient behaviors. This study was conducted to investigate the effects of Happy Spiritual Intervention on the intolerance to uncertainty among families of patients with mental disorders. A pre-post quasi-experimental study with a control group was carried out among families of patients undergoing treatment at Dr. Amino Gondohutomo Psychiatric Hospital in Semarang. Simple random sampling was applied to recruit a total of 50 respondents who were aged 18 years or older and had been cohabiting with the patients for more than five months. The intervention group received six 45-minute therapy sessions, while the control group received standard care. This study utilized the Intolerance of Uncertainty Scale as research instrument. Data were collected using Google Forms, and subsequent analysis using a t-test was performed. The results revealed a significant difference in intolerance of uncertainty among families of patients with mental disorders after the intervention in both the intervention and control groups, with an effect size of 3.026 and a p-value of 0.000. This suggests that Happy Spiritual intervention effectively reduces the intolerance of uncertainty among families of patients with mental disorders.